2017
DOI: 10.2106/jbjs.16.01215
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Orthopaedic Surgeons: A Challenge for Leaders, Learners, and Colleagues

Abstract: Burnout, depression, suicidal ideation, and dissatisfaction with work-life balance have been reported in all medical specialties and at all stages of medical education and practice experience. Burnout consists of progressive emotional, attitudinal, and physical exhaustion. Physicians with burnout may treat patients as objects and feel emotionally depleted. Burnout is characterized by a loss of enthusiasm for work (emotional exhaustion), feelings of cynicism (depersonalization), and a low sense of personal acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 56 publications
2
62
0
2
Order By: Relevance
“…2,8,9 Suicidal ideation in orthopaedic surgery (3.8%) was lower than previously published reports in surgery (7%). 10 Psychological distress in orthopaedic surgery was lower than previously published reports (19%-33%) with no participants scoring for tentative diagnosis of depression. 11,12 Regarding burnout, 20% of individuals endorsed emotional exhaustion (I feel burned out from my work) and 16% reported depersonalization (I have become more callous toward people since I took this job).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…2,8,9 Suicidal ideation in orthopaedic surgery (3.8%) was lower than previously published reports in surgery (7%). 10 Psychological distress in orthopaedic surgery was lower than previously published reports (19%-33%) with no participants scoring for tentative diagnosis of depression. 11,12 Regarding burnout, 20% of individuals endorsed emotional exhaustion (I feel burned out from my work) and 16% reported depersonalization (I have become more callous toward people since I took this job).…”
Section: Discussionmentioning
confidence: 53%
“…20 One trial of subject-focused mindfulness and resilience intervention with biweekly sessions found that the intervention group had reduced depersonalization and emotional exhaustion after 1 year. 10 Implementing these strategies during a pandemic will prove challenging and further studies providing evidence of efficacy should be performed.…”
Section: Discussionmentioning
confidence: 99%
“…15 As these initiatives and pressures have increased administrative workload and decreased reimbursement to physicians and facilities, physician burnout has increased, with cost savings becoming a necessary goal. [16][17][18][19][20] The future uncertainties in healthcare and rising administration challenges may be why most respondents obtained the degree within the past decade (66.6%). This study highlights that orthopedic surgeons are actively taking on additional administrative responsibilities with the addition of an MBA.…”
Section: Discussionmentioning
confidence: 99%
“… 2 - 4 , 10 , 17 Within orthopaedic surgery, burnout has been reported to occur at alarming rates in multiple practice settings (40% to 60%), and has been found to be more prevalent in trainees and early career surgeons than in older surgeons. 18 - 32 …”
Section: Introductionmentioning
confidence: 99%